Cichlid fishes are promising underutilized models to investigate helminth-host-microbiome interactions - Vanhove, Maarten P. M.; Koblmüller, Stephan; Fernandes, Jorge M. O.; Hahn, Christoph; Plusquin, Michelle; Kmentová, Nikol (Frontiers in Immunology, 2025)
The “Old Friends Hypothesis” suggests insufficient exposure to symbionts hinders immune development, contributing to increased immune-related diseases in the Global North. The microbiome is often the focus; helminths, potentially also offering health benefits, lack attention. Infection and effect of helminths are influenced and perhaps determined by micro-organisms. Mechanisms behind parasite-microbiome interactions are poorly understood, despite implications on host health. These interactions are typically studied for single helminth species in laboratory animal models, overlooking helminth diversity. Reviewing research on relationships between helminth and microbial diversity yielded 27 publications; most focused on human or other mammalian hosts, relying on natural exposure rather than experimental helminth inoculation. Only about half investigated host health outcomes. Remaining knowledge gaps warrant considering additional candidate model systems. Given the high helminthiasis burden and species diversity of helminths, we propose seeking models in the Global South, where a considerable proportion of research on diversity aspects of helminth-microbiome interactions took place. Low availability of genomic resources for helminths in the Global South, however, necessitates more integrative helminthological research efforts. Given substantial similarities in immune systems, several fishes are models for human health/disease. More effort could be done to establish this for cichlids, whose representatives in the African Great Lakes provide a well-delineated, closed natural system relevant to human health in view of fish-borne zoonoses and other water-borne parasites. A good baseline exists for these cichlids’ genomics, parasitology, and microbiology. We suggest exploring African Great Lake cichlids as model hosts for interactions between microbial diversity, helminth diversity, and host health.